A Bibliometric Analysis of the Challenges and Opportunities of Fintech in Promoting Access to Sharia Finance - Judijanto, Loso; Muhtadi, Muhamad Ammar; Priyana, Yana (Westscience Press, 2024)
The convergence of financial technology (fintech) and Sharia finance has garnered significant attention in recent years, promising enhanced accessibility and inclusivity in Islamic financial practices. This bibliometric analysis delves into the challenges and opportunities presented by fintech in promoting access to Sharia finance. Spanning from 2017 to 2024, the analysis encompasses 991 papers, revealing a high level of collaboration and a diverse thematic landscape. Key findings highlight the centrality of regulatory frameworks, regional dynamics, and the compatibility of fintech innovations with Sharia principles. Emerging trends, such as the exploration of innovative lending practices and regulatory oversight, underscore the evolving nature of research in this domain. The insights derived from this analysis provide valuable guidance for stakeholders invested in advancing Islamic finance and fintech innovation.